2019
DOI: 10.3389/fped.2019.00390
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis in a Child With the Hyper-IgM Variant of Ataxia-Telangiectasia

Abstract: A subset of patients with Ataxia-Telangiectasia (A-T) have dramatically reduced levels of IgG, IgA, and IgE with retained or elevated IgM levels. Several reports suggest that these A-T patients with a “hyper-IgM phenotype” (HIgM) suffer more clinical immunologic consequences than other A-T patients. The immunopathologic mechanism driving this phenomenon is unknown, making it difficult to predict response to immunomodulatory therapy. We describe an A-T patient with HIgM who underwent tumor necrosis factor (TNF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the opportunistic pathogen, Pseudomonas aeruginosa which was cultured exclusively in patients with the HIGM A-T variant, is associated with a more severe course of lung disease and a higher risk of chronic respiratory failure ( 16 , 49 ). In our group of HIGM A-T children, impaired CSR was associated with more severe clinical phenotypes, including autoimmune phenomena, granulomatous disorders, inflammatory organ-specific immunopathology, lymphoproliferation, and malignancy, consistently with previous reports ( 18 , 24 , 33 , 34 ). Whereas in three out of all the six HIGM A-T patients, Epstein-Barr virus (EBV)-DNA was persistently identified in peripheral blood pointing to the EBV reactivation, important concerns are raised regarding the role of the dysfunctional ATM kinase activity in favoring the EBV life cycle and promoting lymphoproliferation and malignancy in immunocompromized A-T individuals ( 50 , 51 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the opportunistic pathogen, Pseudomonas aeruginosa which was cultured exclusively in patients with the HIGM A-T variant, is associated with a more severe course of lung disease and a higher risk of chronic respiratory failure ( 16 , 49 ). In our group of HIGM A-T children, impaired CSR was associated with more severe clinical phenotypes, including autoimmune phenomena, granulomatous disorders, inflammatory organ-specific immunopathology, lymphoproliferation, and malignancy, consistently with previous reports ( 18 , 24 , 33 , 34 ). Whereas in three out of all the six HIGM A-T patients, Epstein-Barr virus (EBV)-DNA was persistently identified in peripheral blood pointing to the EBV reactivation, important concerns are raised regarding the role of the dysfunctional ATM kinase activity in favoring the EBV life cycle and promoting lymphoproliferation and malignancy in immunocompromized A-T individuals ( 50 , 51 ).…”
Section: Discussionsupporting
confidence: 91%
“…The leading A-T symptomatology is characterized by neurodegeneration and progressively debilitating cerebellar ataxia with postural instability, oculomotor apraxia, dysarthria and orolingual insufficiency, as well as extrapyramidal dysfunctions with choreoathetotic movements, dystonia and muscle tremor ( 4 , 10 12 ). The extended disease phenotype also includes chronic obstructive airway and interstitial lung disease ( 13 16 ), chronic inflammatory non-alcoholic liver disease ( 17 20 ), cutaneous and systemic granulomatosis ( 21 24 ), and hormonal dysfunctions with growth retardation, gonadal insufficiency, and diabetogenic insulin resistance ( 25 27 ). The impaired thymic T cell production, defective B cell development accompanied by hypogammaglobulinemia, IgG subclass and antigen-specific antibody generation, and bone marrow failure contribute to a combined immunodeficiency ( 28 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Except for case 3 of the present study, all reported patients with autoimmunity and cutaneous granuloma presented with HIgM phenotype along with splenomegaly. The etiology of these complications is not welldefined, but it seems that reduced regulatory T cells and increased ratios of CD21 −/low B cells, as well as disturbed naïve T and B cells along with splenomegaly, could be attributed to these patients (64)(65)(66). However, in our 3 evaluated cases, despite a decrease in naïve and regulatory T cells, nobody had an increase in CD21 −/low B cells.…”
Section: Discussionmentioning
confidence: 59%
“…Similar to cases 1 and 2 in the present study 10% of variant patients presented HIgM phenotype, as all were homozygous for a truncating mutation predicting the absence of ATM protein. The HIgM phenotype of AT is also associated with autoimmunity and cutaneous granulomatous disease (65)(66)(67)(68). Except for case 3 of the present study, all reported patients with autoimmunity and cutaneous granuloma presented with HIgM phenotype along with splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…53 The latter group of patients, with a "hyper-IgM phenotype" is characterized by an elevated IgM level, which is, alike high alpha-fetoprotein (AFP) level, a marker for a more severe immune dysfunction, dysregulation, and autoimmune phenomena, increased infection risks and progressive liver disease. [54][55][56] Immunodeficiency in A-T is associated with a high risk of malignancies, most frequently B cell non-Hodgkin lymphoma (NHL), Hodgkin lymphoma (HL), and T cell acute lymphoblastic leukemia (ALL), which occur at a high rate and at early age, and shorten the survival. 56 A broad spectrum of clinical phenotypes with numerous infectious and variable noninfectious complications, as well as organ-specific pathologies in A-T, requires pediatrician's special attention, multidisciplinary approach, and careful management of affected children.…”
Section: Charge Syndromementioning
confidence: 99%